Sea Buckthorn (Hippophae rhamnoides L.) and Quince (Cydonia oblonga L.) Juices and Their By-Products as Ingredients Showing Antimicrobial and Antioxidant Properties for Chewing Candy: Nutraceutical Formulations - Vita Lele; Ema Monstaviciute; Ieva Varinauskaite; Gabriele Peckaityte; Laura Paskeviciute; Monika Plytnikaite; Vitalija Tamosiunaite; Meda Pikunaite; Modestas Ruzauskas; Rolandas Stankevicius; Elena Bartkiene (Journal of Food Quality)
Sustainable and environmentally friendly approaches to the production of health foods have become very popular. The concept of this study was to develop chewing candy (CC)—nutraceutical formulations based on sea buckthorn (Hippophae rhamnoides L.) and quince (Cydonia oblonga L.) juice and juice by-products (BuJ, QuJ, BuBP, and QuBP, resp.), as ingredients showing antimicrobial properties against Klebsiella pneumoniae, Salmonella enterica, Pseudomonas aeruginosa, Acinetobacter baumannii, Proteus mirabilis, methicillin-resistant Staphylococcus aureus (MRSA), Enterococcus faecalis, E. faecium, and Bacillus cereus. Two texture-forming agents (agar and gelatin) were tested for CC formulation. BuJ, QuJ, BuBP, and QuBP showed antimicrobial activity against all the pathogens tested, and the largest inhibition zones against Bacillus and Proteus mirabilis were observed for BuJ and QuJ, respectively. Agar and/or gelatin selection has a significant influence on CC texture (p=0.0001), and interactions of agar and/or gelatin selection × juice or juice by-products and sea buckthorn or quince × juice or juice by-products were also significant (p=0.0001). The best acceptability was shown for CC prepared with agar and BuBP (131.7) and with gelatin and QuJ (132.0). The addition of BuJ, QuJ, BuBP, and QuBP increases the antioxidant activity of CC by five times. Finally, not just juice, but also juice by-products, have great potential as desirable antimicrobial ingredients for the food industry.